Modification of Chitosan-Chitosan Phtalate Anhydrides Matrices - Lukman Atmaja; Herianus Manimoy; Lina Eka Arizka (IPTEK The Journal for Technology and Science, 2019)
Chitin and chitosan are natural biopolymers on shrimp shells. Chitosan is used extensively as a raw material in various industries. The study aimed to extract chitin and chitosan from fanami shrimp skin through deproteinization, demineralization, and deastilation reactions and to modify the matrix to improve the physical properties. The results of the analysis of the FTIR chitin spectrum shows several major peaks at wave number 3446.91 cm-1 which showed the vibrations of bending secondary amide and amine (NH) secondary amides at 1654.98 cm-1 indicating the presence of vibration stretching CH. The results of the chitosan FTIR spectrum analysis shows symmetrical stretching vibrations at 3433.41 cm-1 due to overlapping OH and amines (NH), stretching vibrations of 1653.05 cm-1 caused by the propagation of C = O stretching and stretching vibrations of 1587.47 cm-1 indicating secondary amide. The results of the characterization with XRD shows that the extracted compounds were chitin and chitosan. In modifying the chitosan matrix, the spectra result show peak at 1656.91 - 1564.32 cm-1 indicating the presence of an amide group. New aromatic group peak found in the area of 1631.83 cm-1 which not found in chitosan. Diffract gram XRD from pure chitosan shows three highest peak peaks at 2θ equal to 609.2; 609.88 and 550 while chitosan-anhydrous modification shows a peak at 2θ equal to 609.8. The addition of anhydrous phthalates to chitosan has reduced its crystallinity which results in an increase in the hydrophilic characteristics of the membrane. The results of this study are expected to be one of the references in further research regarding the manufacture of phthalate chitosan-anhydrous based composite membranes for DMFC